ELDERLY CARE SERVICE MANAGEMENT IN THE CONTEXT OF SOCIAL ENTERPRISE - Chanchanakit, Chitra (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
Entering the ageing society is both a problem and an opportunity. The problems are the increase of economic dependency, and the resources allocation of government to support ageing health care. From the opportunity view, this issue is knowledge retention- a soft asset of the organization. Caring business for the elderly as the social enterprise context leads to enhance the quality of life and society. The study conducts on the synthesis of the previously studied, and then confirmatory analysis proves by using 150 elderly sample units in the “Sawangkanives” project. The results show that “Standardization Care” is the most significant effect on “Healthy Ageing” with a value of 0.286. Moreover, the testing of “Engagement” as the mediator between “Harmony Care” and “Healthy Ageing” support by the Sobel test.